(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
Radio journalism remains one of the most influential forms of mass communication due to its ability to provide timely and accessible information to diverse audiences. The effectiveness of radio broadcasting largely depends on the professional skills of journalists in collecting, verifying, editing, and presenting information. This study examines the role of journalistic mastery in radio information programs through an analysis of Ovozi Tojik Radio. The research explores the relationship between journalistic facts, information genres, and professional competence in radio journalism. Special attention is given to news headlines, information structure, editing techniques, the use of numerical data, and audience engagement strategies. The findings demonstrate that concise language, effective genre selection, accurate fact presentation, and professional editing significantly enhance the communicative effectiveness of radio news. The study concludes that journalistic mastery remains a fundamental factor in ensuring objectivity, credibility, and audience trust in contemporary radio broadcasting.